SELF EFFICACY MAHASISWA PENDIDIKAN MATEMATIKA DALAM MEMECAHKAN MASALAH GEOMETRI - Setia Widia Rahayu (Almeera Education, 2025)
This study aims to describe the self-efficacy of mathematics education students in solving geometry problems. This study is a descriptive qualitative study with research subjects, namely one student with a high self-efficacy classification and one student with a low self-efficacy classification. The instruments used in this study consisted of a self-efficacy questionnaire, problem-solving ability test, interview guidelines, and documentation that had been adjusted to Polya's self-efficacy criteria in problem solving. Based on the results of the study, it was obtained that students' self-efficacy in solving geometry problems met all stages of Polya's problem solving, namely: (1) understanding the problem; (2) making a solution plan; (3) implementing the solution plan; and (4) looking back. In practice, masculine subjects have high confidence in their ability to solve mathematics problems.